An Experimental Study on Settlement due to the Mutual Embedding of Miscellaneous Fill and Soft Soil - Fuhai Zhang; Lei Zhang; Tianbao Zhou; Lijun Duan; Chong Shi (Advances in Civil Engineering)
Settlement deformation in the foundation with miscellaneous fill and soft soil was typically calculated by summing up the settlement in each individual layer. However, this calculation method did not involve settlement deformation by embedding miscellaneous fill particles into soft soils under external loads, thus inducing significant settlement prediction error. To solve this problem, a laboratory testing device was developed to study the mutual embedding for specimens with different miscellaneous fill particle sizes, external loads, and particle materials. Testing results indicate that a larger particle size and subsequently the smaller specific surface resulted in greater mutual embedding settlement due to the smaller resistance. In addition, higher external loads and smaller interface friction both induced larger settlement. Based on these results, a theoretical calculation equation of settlement due to the mutual embedding of miscellaneous fill and soft soil was proposed. The calculated settlements were found to be well matching with the experimental results.